Pengaruh Earning Per Share Dan Return On Assets Terhadap Harga Saham: (Studi Pada PT. Hanjaya Mandala Sampoerna Tbk) - Marniati Marniati; Ellyn Patadungan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of earnings per share and return on assets on stock prices (studies at PT. Hanjaya Mandala Sampoerna Tbk). The research problem in this study is whether Earning Per Share (EPS) and Return On Assets (ROA) partially and simultaneously affect the stock price at PT. Hanjaya Mandala Sampoerna Tbk. The research method uses the Multiple Linear Regression analysis technique with SPSS version 26. Based on the results of the analysis, it can be concluded that partially the Earning Per Share (EPS) variable has a positive and significant effect on stock prices, the Return On Assets (ROA) variable has no effect on prices share. Simultaneously the EPS and ROA variables affect stock prices. The coefficient of determination (R2) in this study is 0.810, meaning that EPS and ROA affect stock prices by 81% and the remaining 19% is influenced by other variables not included in this study.